Integrating Sakubun Writing Instruction with Character Education: A Case Study in Japanese Language Pedagogy - Runtuwarouw, Jourike; Bintang Pratiwi Harahap, Putri; Sambe, Nozomi (IJORER : International Journal of Recent Educational Research, 2026)
Objective: This study investigates the integration of sakubun writing instruction with character education in Japanese language pedagogy at Manado State University, exploring implementation strategies and student responses to this integrated approach. A qualitative descriptive design was employed with 30 fifth-semester students as participants. Data were collected through classroom observations (12 sessions), semi-structured interviews (15 students), and document analysis of sakubun compositions. Thematic analysis was used to identify patterns in integration practices and student perceptions. Findings reveal three primary integration strategies: thematic writing assignments incorporating moral values, reflective journal activities, and collaborative peer feedback emphasizing respectful communication. Students demonstrated enhanced awareness of character values such as honesty, responsibility, and empathy while developing their Japanese writing proficiency. Students reported increased motivation and meaningful engagement in writing tasks. Key challenges included time constraints and difficulty in assessing character development alongside linguistic competence. This study provides empirical evidence of character education integration within Japanese writing pedagogy, an underexplored area in foreign language education research. It offers a practical framework for language educators seeking to implement values-based instruction while maintaining focus on linguistic objectives, contributing to holistic approaches in second language writing instruction.